Pendekatan Bimbingan Individu untuk Mengatasi Kesulitan Membaca pada Siswa Kelas Tinggi SD GMIT Betun III - Maria Delarista Lau; Yanuarius Bria Seran; Yohana Febriana Tabun; Marianus Teti (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Reading ability is a fundamental skill that elementary school students must possess because it serves as the foundation for understanding all learning subjects. However, many upper-grade students still experience reading difficulties, including recognizing letters, combining sounds into words, reading fluently, and comprehending reading texts. This study aimed to identify the dominant types of reading difficulties experienced by upper-grade students at SD GMIT Betun III and to describe the implementation of an individual guidance approach in overcoming these difficulties.This research employed a descriptive qualitative approach. The research participants consisted of the principal, fourth-, fifth-, and sixth-grade teachers, and upper-grade students experiencing reading difficulties. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed the Miles, Huberman, and Saldana interactive model, including data reduction, data display, and conclusion drawing.The findings revealed that students experienced phonological difficulties, difficulties in recognizing letters and words, lack of reading fluency, and difficulties in understanding sentence structures. The implementation of individual guidance involved problem identification, diagnosis, planning, individualized reading assistance, motivational support, evaluation, and follow-up activities. This approach significantly improved students' reading skills, confidence, learning motivation, and reading comprehension Therefore, the individual guidance approach is considered an effective strategy for helping elementary school students overcome reading difficulties because it provides personalized learning assistance according to each student's needs.